Geochemical assessment of Naopurdan limestone for cement making - Chwarta area, Kurdistan Region, NE Iraq - Mirza, Tola A.; Mohialdeen, Ibrahim M. J.; Al-Hakarri, Salim H.; Fatah, Chro M. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The Naopurdan limestone klippe is covering about 19.28 Km2 of Chwarta area-Sulaimani City. Fifteen samples were collected from this limestone body and analyzed by X-ray fluorescence technique. The analysis was carried out in Mass Cement Company. The Petrographical study revealed the presence of different fossil content such as Nummulitesspp ( N. perforates; N.milliucaput; N.globulosa; N.atacicus; N.bahyranses)., Alvelinaspp( A. eleptica; A. aragoensis; A. oblonga; A. fusiformis)., Miliolina ; Algae (Lithothaminum sp.; Cympolina sp. ); echinoid bioclasts; corals; and Orbitolites; Coskinolinasp; Somalina sp. Index fossils indicate the Middle Eocene age for this limestone body. The formaniferal wackestone and packstone microfacies are the most common facies in the studied samples, as well as recrystallized limestone observed in two samples. The depositional environment as deduced from lithology and fossil content is shoal marine environment. Petrological study indicated that the limestone samples are crystalline and dominantly composed of calcite with CaCO3 content more than 95 %. Geochemical analysis results of fifteen handpicked samples indicated that the limestone from the Naopurdan Formation shows LOI range between (38.50% to 43.29%), Si02 (0.11% to 7.92%), CaO (55.19% to 45.82%), A12O3(0.01% to 0.97%), Fe2O3(0.02 % to .46%) and MgO 0.37 % to 4.29 %,K2O,Na2O, and SO3 are present in traces. The lime saturation factors (LSF) of studied samples have widely differing values ranging from 188.64 to 7543.52, but most have values above the limits required for high quality cement. Thus a claystone rocks from Red Bed Series have been added to reach the best point of LSF of clinker. All materials after mixing proved that they meet the specification required for clinker production.
Keywords: Naopurdan; Red BedSeries; Limestone,Cement; Limesaturation factor